The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/bjc.2013.35
|View full text |Cite
|
Sign up to set email alerts
|

A randomised double-blind placebo-controlled phase II study of AGI004 for control of chemotherapy-induced diarrhoea

Abstract: Background:AGI004 is a controlled-release transdermal patch preparation of mecamylamine. We conducted a randomised placebo-controlled phase II study of two dose levels of AGI004 in chemotherapy-induced diarrhoea (CID).Methods:Adult patients receiving chemotherapy who had experienced diarrhoea (NCI grade 1–2) during previous cycles of chemotherapy were eligible. In all, 64 patients were randomised to receive AGI004 4 mg then 8 mg per 24 h transdermal patch or placebo for two sequential cycles of chemotherapy. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The incidence of chemotherapy-induced diarrhea has been reported as high as 50-80% in patients undergoing systemic chemotherapy [13]. 31% of patients undergoing chemotherapy for colorectal cancer experience diarrhea severe enough to require dose delay/reduction, and patient hospitalization [14,13,15]. Studies have shown that chemotherapeutic drugs increase intestinal permeability and modulate gut microbiota, which collectively contribute to CIGT [12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of chemotherapy-induced diarrhea has been reported as high as 50-80% in patients undergoing systemic chemotherapy [13]. 31% of patients undergoing chemotherapy for colorectal cancer experience diarrhea severe enough to require dose delay/reduction, and patient hospitalization [14,13,15]. Studies have shown that chemotherapeutic drugs increase intestinal permeability and modulate gut microbiota, which collectively contribute to CIGT [12,16].…”
Section: Introductionmentioning
confidence: 99%